Sedation Free Colonoscopy: Patients’ Characteristics and satisfaction in a hospital based Endoscopy Unit - Kumar, Amit; Pathak, Rahul (Journal of Advances in Internal Medicine, 2017)
Background and aims: Colonoscopy without sedation costs less and is more convenient than sedated colonoscopy and is the main mode of examination in our settings. The aims of the present study is to determine the percentage of patients who can successfully undergo unsedated colonoscopy and the factors contributing to patient satisfaction following the examination. Material and Methods: Demographic, clinical, and colonoscopy related data were prospectively evaluated in 113 patients undergoing unsedated colonoscopy by an experienced endoscopist during the period of October 2015 to January 2016 at a single hospital based endoscopy setup. All colonoscopies routinely began without sedation and was curtailed if the patient or physician desired. Age, sex, prior abdominal operation, pain during examination and the time required to complete the colonoscopy were recorded. The patients were asked to rate their pain on scale of 0 to 10, their satisfaction and willingness to undergo colonoscopy without sedation in future if required. Results: In a total of 113 patients (mean age of 54.01 years) undergoing sedation free colonoscopy, 108 (95.5%) required no sedation. Complete colonoscopy was done in 106 of the 108 and 110 of the 113 patients. The mean pain score was 2.58 in an average time taken of 11.9 minutes. Average time for intubation taken in post-operative patients (n=20) was 12.24 minutes. 96(84.9%) of the patients were completely or well satisfied with the examination and 7(6.2%) were not satisfied with the procedure. There was not much difference in pain perception or satisfaction based on gender. Conclusion: Colonoscopy without sedation can be completed successfully in a vast majority of patients with proper technique by experienced endoscopist. The practice saves time and money and patients are willing to return for future examinations if required. The facility of sedation should be present if required for any reason.